Interoperability and Public Value Creation in Digital Government: Rethinking Institutional Design for Integrated Service Delivery - Fatmawati A Rahman; Jasruddin Daud; Rifdan Rifdan; Wahira Wahira (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
Interoperability has become a critical enabler of integrated service delivery in contemporary digital government. However, despite significant technological investments, many governments continue to experience fragmented service systems and limited public value outcomes. This study examines how institutional design shapes interoperability capacity and how interoperability contributes to public value creation within digital government frameworks. Employing a qualitative explanatory case study approach, data were collected through semi-structured interviews, document analysis, and institutional observations. The findings reveal that interoperability is not solely a technical function but an institutional capability embedded in governance structures, regulatory frameworks, data standards, and coordination mechanisms. While technical data exchange mechanisms exist, institutional fragmentation, regulatory ambiguity, and limited cross-agency collaboration constrain seamless integration. The study demonstrates that institutional design mediates the relationship between interoperability and public value creation by influencing the effectiveness of integrated service delivery. Public value gains are evident in operational efficiency and accessibility; however, improvements in legitimacy, trust, and service coherence remain incremental where institutional alignment is weak. The research contributes to digital governance literature by conceptualizing interoperability as an institutional construct and highlighting the necessity of governance reform for sustainable public value generation. The findings suggest that governments must prioritize institutional coherence, standardized data governance, and collaborative coordination frameworks to fully realize the transformative potential of digital government.